Взаємовідносини «емоційних» роботів і людини - Гриненко, А. О. (ХНУРЕ, 2022)
Robotics is developing rapidly, and robots have already become invaluable production assistants. We are on the cusp of a revolution in robotics right now. According to one of the possible scenarios, robots will become our best friends. This scenario is only possible if the robots have empathy. But can machines have empathy? What would be the interaction between man and machine if the robot could show feelings and have empathy? What problems can humanity face in this case? And is it worth continuing to develop “emotional” robots?
Keywords: «емоційний» робот